Mathematical Formulation and Theoretical Background of Harmful-Particle Separation in Multicyclones - Djurayev Sherzod Sobirjonovich (Scientific Trends, 2025)
This paper presents an extended mathematical framework for predicting the removal of hazardous dust and aerosol particles in multicyclone separators. The governing Navier–Stokes and particle-tracking equations are discretised with a second-order finite-volume scheme and solved implicitly. Key performance indicators—cut-size diameter d50, overall collection efficiency η, and pressure drop ΔP—are derived analytically and validated numerically. Expanded results show that, at equal pressure loss, a multicyclone operating at an inlet velocity of 12 m s⁻¹ captures 95 % of particles larger than 5 μm while consuming 22 % less fan power than an equivalent single cyclone. Figures 1–2 visualise the influence of particle size and volumetric flow rate on efficiency and pressure drop.
Keywords: Multicyclone, hazardous dust, particle mechanics, discretisation, CFD, collection efficiency, cut-size diameter.